Effectiveness of an Educational Program on Nurses Knowledge about Nosocomial Infection: Case- Control Study - Saad A. Jissir; Huda B. Hassan (Kufa Journal for Nursing Sciences)
Objectives: the present study aims to find out the effectiveness of an educational program concerning the nurse's knowledge about nosocomial infection, and to find out the relationship between effectiveness of program and nurses year of experiences, level of education, and training course.